Electrochemistry of Graphene Nanoplatelets Printed Electrodes for Cortical Direct Current Stimulation - Pepłowski, Andrzej; Rathi, Sanchit; Piotrkowski, Bartosz; Ziółkowski, Robert; Janczak, Daniel; Krzemiński, Jakub; Brosch, Michael; Jakubowska, Małgorzata (Frontiers in Neuroscience, 2020)
Possible risks stemming from the employment of novel, micrometer-thin printed electrodes for direct current neural stimulation are discussed. To assess those risks, electrochemical methods are used, including cyclic voltammetry, square-wave voltammetry and electrochemical impedance spectroscopy. Experiments were conducted in non-deoxidated phosphate-buffered saline to better emulate living organism conditions. Since preliminary results obtained have shown unexpected oxidation peaks in 0-0.4 V potential range, the source of those was further investigated. Hypothesized redox activity of printing paste components was disproven, supporting further development of proposed fabrication technology of stimulating electrodes. Finally, partial permeability and resulting electrochemical activity of underlying silver-based printed layers of the device were pointed as source of potential tissue irritation or damage. Employing this information, electrodes with corrected design were investigated, yielding no undesired redox processes.